In search of Paul : how Jesus's Apostle opposed Rome's empire with God's kingdom : a new vision of Paul's words & world - Crossan, John Dominic; Reed, Jonathan L. (San Francisco, HarperSanFrancisco, 2004)
Presents archaeological evidence and historical analysis to answer questions about Paul and the early Christians, contending that Paul worked for justice and equality against the oppressive power of the Roman Empire.
Preface: Paul for a new millennium -- Prologue: The hope of a peaceful earth -- Jewish faith and pagan society --
Includes bibliographical references (pages 415-420) and index.
Keywords: Paul, -- the Apostle, Saint; Church history -- Primitive and early church, ca. 30-600.